Comparison of the Pedicled Latissimus Dorsi Flap with Immediate Fat Transfer versus Abdominally Based Free Tissue Transfer for Breast Reconstruction. Issue 2 (August 2020) - Black, Cara K.; Zolper, Elizabeth G.; Economides, James M.; Abadeer, Andrew; Fan, Kenneth L.; Song, David H.
Abstract : Background: Abdominally based free tissue transfer (FTT) and latissimus dorsi and immediate fat transfer (LIFT) procedures are both fully autologous options for breast reconstruction. The former is specialized and requires comfort with microsurgical technique, whereas LIFT combines a common set of techniques familiar to all plastic surgeons. Comparing the two methods for clinical effectiveness and complications for equivalency in outcomes may help elucidate and enhance patient decision-making. Methods: A retrospective review of a prospectively maintained database between March of 2017 and July of 2018 was performed to compare the LIFTs and FTTs performed by the senior surgeon. Outcomes of interest included postoperative complications, flap success, and follow-up revision and fat-grafting procedures. Results: Sixty-five breasts were reconstructed by FTT; and 31 breasts were reconstructed with LIFT. Demographics were similar ( p > 0.05). LIFT had a shorter length of operation time (343 ± 128 minutes versus 49 ± 137 minutes) ( p < 0.0001) and a shorter length of stay (1.65 ± 0.85 days versus 3.83 ± 1.65 days) ( p < 0.001). FTTs had a shorter time until drain removal (13.3 ± 4.3 days versus 24.0 ± 11.2 days) ( p < 0.0001). The number of major (requiring operation) and minor complications were not statistically different (i.e., FTTs, 20.0 percent major and 27.7 percent minor; LIFT, 12.9 percent major and 19.35 percent minor) ( p > 0.05). The need for revisions (FTTs, 0.80 ± 0.71; LIFT, 0.87 ± 0.71) and fat grafting (FTTs, 41.54 percent; LIFT, 58.8 percent) was not statistically different ( p > 0.05). Conclusions: Both the LIFT and abdominally based FTT have similar outcomes and complication rates. However, LIFT may be preferred in patients who require shorter operation times. The LIFT may be the fully autologous breast reconstruction of choice for nonmicrosurgeons. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : Supplemental Digital Content is available in the text.